2009
DOI: 10.1007/s00066-009-1937-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome and Prognostic Factors in Early-Stage Nodal Low-Grade Non-Hodgkin’s Lymphomas Treated with Radiation Therapy

Abstract: Radiotherapy of early-stage low-grade NHL is a curative therapy option, particularly in younger patients and patients with follicular histology. Relapse analysis confirmed the benefits of total nodal or total lymphatic irradiation, although the small number of patients needs to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
14
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 34 publications
(54 reference statements)
5
14
0
2
Order By: Relevance
“…Radiotherapy was added to treatment protocol of the patient after 4 cycles of chemotherapy due to equal efficacy in remission and higher efficacy for consolidation of 4 cycles of chemotherapy plus radiotherapy when compared to 8 cycles of chemotherapy in the early stage of lymphoma (stage I or II) according to literature. 11,12 Rheumatoid disease is associated with an increased risk of developing lymphoma, even in patients who are not treated with immunosuppressive therapy. Since spontaneous remission of lymphoma after immunosuppressive drug withdrawal has been documented, it has been speculated that immunosuppressive therapy is likely to be an additional factor for lymphoma development.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy was added to treatment protocol of the patient after 4 cycles of chemotherapy due to equal efficacy in remission and higher efficacy for consolidation of 4 cycles of chemotherapy plus radiotherapy when compared to 8 cycles of chemotherapy in the early stage of lymphoma (stage I or II) according to literature. 11,12 Rheumatoid disease is associated with an increased risk of developing lymphoma, even in patients who are not treated with immunosuppressive therapy. Since spontaneous remission of lymphoma after immunosuppressive drug withdrawal has been documented, it has been speculated that immunosuppressive therapy is likely to be an additional factor for lymphoma development.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal treatment volume of radiotherapy is still discussed controversy and there are only few studies comparing different radiation volumes in the literature [6,7,8,10,13]. Some studies showed increased rates of out-of field relapses when smaller irradiation fields were used [10,17,23].…”
Section: Discussionmentioning
confidence: 99%
“…In stage I and II low-grade B-cell lymphoma with good prognostic factors, radiotherapy is the standard treatment, achieving local control rates of 95% and 50% of the patients are relapse free at 10 years [6,13,17,21,23,30]. In patients with more aggressive histologies and/ or advanced stages, the application of CHOP (cyclophosphamide, doxorubicin, vincrstine, and prednisone) chemotherapy with or without RT showed 5-year survival rates of 68-95% [14,19,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 20% of patients are diagnosed in the early Ann Arbor stages I and II. For Ann Arbor stage I-II and limited stage III patients, radiotherapy (RT) is a curative option [2,24,25,26,27], as FL is one of the most radiosensitive malignancies known. As most FL patients are diagnosed in stage III or IV, only a few studies have reported the results of RT in the management of stage I and II FL (.…”
mentioning
confidence: 99%